2020
DOI: 10.1556/2066.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, awareness, and usage of probiotics among Hungarian adults: An explorative survey

Abstract: PurposeThe aim of this study was to evaluate the use of probiotic products in Hungary, to explore consumers' knowledge of probiotics, and to gain information about the main characteristics of current usage.Materials and MethodsThe research used a self-developed explorative questionnaire to obtain the necessary information. The data collected was further analysed with IBM SPSS 25.0 and Microsoft Office Excel.ResultsNearly three-quarters of respondents (73.9%) have used probiotics in their life. Those who have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
2
1
0
1
Order By: Relevance
“…Gastrointestinal complaints have increased due to the widespread use of antibiotics and associated side effects on the gut microbiota (21). And, as expected, in this current study experienced obstetricians recommended probiotics more during pregnancy, most frequently for gastrointestinal tract symptoms and flora regulators, respectively in line with the previous studies (19).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Gastrointestinal complaints have increased due to the widespread use of antibiotics and associated side effects on the gut microbiota (21). And, as expected, in this current study experienced obstetricians recommended probiotics more during pregnancy, most frequently for gastrointestinal tract symptoms and flora regulators, respectively in line with the previous studies (19).…”
Section: Discussionsupporting
confidence: 85%
“…Studies have shown that there is a desire and need to obtain more reliable information about these products (15). Although the main sources of information were affected by the cultural and economic conditions of the countries, similar to our study Internet was reported to be used more frequently (18,19). To our knowledge, there is no microbiota, probiotic or prebiotic lecture during the residency training program process and also during medical schools as to the role of these biotherapeutics to be used as a medication.…”
Section: Discussionsupporting
confidence: 84%
“…10 Literatürde probiyotiklerin gastrointestinal sistem sağlığını iyileştirmek, bağışıklık sistemini güçlendirmek ve diyare semptomlarını azaltmak amacıyla kullanıldığı belirtmektedir. 19 Çalışmamızda da benzer şekilde ebe ve hemşireler probiyotikleri kullanma nedenlerini bağışıklığı güçlendirmek (%66.8), sağlık geliştirmek (%63.9) ve mide bağırsak sistemini düzenlemek (%62.9) şeklinde belirtmişlerdir.…”
Section: Discussionunclassified
“…Given the study design with a specific setting and inclusion criteria, drawing comparisons with other studies is challenging. Nevertheless, an explorative survey in Hungary found that the most common reasons for using probiotics were to alleviate the side effects of previous antibiotic treatment (87.6%) and the symptoms of diarrhoea (24.5%) [ 18 ]. Similarly, another study by Chin-Lee et al, reported the most common reasons for probiotic use as maintenance of gut health and immune status [ 19 ].…”
Section: Discussionmentioning
confidence: 99%